Pengaruh Konten, Terpaan Media dan Kredibilitas Akun Instagram @tempodotco terhadap Pemenuhan Kebutuhan Informasi Politik Followers - Kamil Anshori; Sugiharti Binastuti (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The use of Instagram social media cannot be separated from the various needs of each user. Instagram is used as a medium for political communication and political education. In addition, Instagram social media is also used as a place to meet the need for political information. One of them is the Instagram account social media @tempodotco which presents various information related to politics. The purpose of this study was to determine and analyze the influence of content, media exposure, and credibility of the Instagram account @tempodotco on the fulfillment of followers' political information needs simultaneously and partially. This study uses a quantitative method sourced from primary data by distributing questionnaires as a data collection instrument. Valid data amounted to 400 people who are followers of the Instagram account @tempodotco which was determined by the Slovin formula using a purposive sampling technique. The results of the study showed that content, media exposure, and credibility significantly influenced the fulfillment of followers' political information needs. The results of the study support the uses and gratification theory which explains that those known as audiences or media users play an active role in choosing and trying to fulfill their needs by finding the best media sources.